Ending hunger by 2030 - Policy actions and costs - von Braun, Joachim; Chichaibelu, Bezawit Beyene; Torero, Maximo; Laborde Debucquet, David; Smaller, Carin (Center for Development Research, Germany, 2020)
The 2030 Agenda for Sustainable Development pledged to move away from growing inequality to more inclusive, shared growth, away from ecocide, mass extinction of our plant and animal biodiversity, and waste and destruction of our planet’s abundant but still finite natural resources to practices that respect and protect our common home, and away from activities that expose hundreds of millions of people to the insidious effects of rising global temperatures and its consequences for climate risks. At the heart of the 2030 Agenda was a promise to prioritize to eradicate poverty and end hunger and malnutrition in all their forms. Too many people in the world today do not have access to sufficient, affordable, safe and healthy foods. About three billion people in the world cannot afford a healthy diet. To address this global challenge, G7 heads of states at their Summit in Elmau in 2015 committed to lifting 500 million people out of hunger and malnutrition by 2030, i.e. 72 percent of the total undernourished in 2019 and 60 percent of the total including COVID-19 projections in 20202, as part of a broader effort to be undertaken with partner countries to support the 2030 Agenda for Sustainable Development, i.e. Sustainable Development Goal 2 (SDG 2) to end hunger and malnutrition by 2030.